Strategi Gereja dalam Menumbuhkan Minat Jemaat untuk Beribadah Melalui Metode Pemuridan - Edison Edison; Talizaro Tafonao; Septerianus Waruwu (Sekolah Tinggi Teologi Baptis Medan, 2022)
AbstractThe purpose of writing this article is to find out what strategies are used by the church in growing the congregation's interest in worship. This paper departs from the problems found by the author since serving the congregation in Kalimantan. The seriousness of the congregation in worship so far has been very insignificant, as a result the growth of the congregation's faith has decreased as explained in this article. The method used in this research is descriptive qualitative research method by collecting data through interviews, empirical data, literature such as books and journal articles that can be trusted. The results obtained in this study are that the church must have a discipleship approach strategy, a realizational model and a counseling model. The three methods proposed by this author are very effective and significant in motivating the congregation to see the various problems experienced by the congregation, especially in worshiping in the church. Thus, the strategy used by the church so far needs a breakthrough because this will determine the congregation's interest in worship. Keywords: Strategy, Church, Congregation Interest, Worship, Discipleship